A nonlocality-based homogenization method for dynamics of metamaterials. (1st September 2022) - Mei, Chaosheng; Li, Li; Li, Xiaobai; Tang, Haishan; Han, Xiangzhen; Wang, Xuelin; Hu, Yujin
Abstract: A nonlocality-based homogenization method and a corresponding framework for calibration of its nonlocal parameters are proposed for periodic metamaterials. The calibration of nonlocal parameters is realized through the analysis of both macroscopic and microscopic representative volume element of metamaterials with periodic boundary conditions. The proposed nonlocality-based homogenization method can be applied to the dynamics such as vibration of structures made of periodic metamaterials on the macroscopic scale. Taking one-dimensional metamaterials as an example, numerical results show that nonlocal parameters are dispersive for metamaterials rather than constant as traditional nonlocal theories indicate. The nonlocality-based homogenization method can accurately predict the eigenfrequencies and band gaps of metamaterial structures in a higher frequency range compared with the traditional homogenization model and the classical nonlocal model. The proposed model provides the possibility to accurately and efficiently simulate the dynamic behaviors of metamaterial structures on the macroscopic scale in wide frequency ranges.